2022
DOI: 10.3390/aerospace9120846
|View full text |Cite
|
Sign up to set email alerts
|

Inlet Gap Influence on Low-Frequency Flow Unsteadiness in a Centrifugal Fan

Abstract: In this study, unsteady low-frequency characteristics in a voluteless low-speed centrifugal fan operating at a high mass flow rate are studied with improved delayed detached eddy simulation (IDDES). This study is motivated by a recent finding that the non-uniformly distributed pressure inside this type of fan could be alleviated by improving the gap geometry. The present simulation results show that the velocity magnitudes of the gap have distinct low and high regions. Intensive turbulent structures are develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
0
0
Order By: Relevance
“…By adjusting the ejector geometry, experiments and numerical simulations showed that the thrust was increased, but the specific fuel consumption and noise emissions were reduced. In addition to the above works, Ottersten et al [9] found a new mechanism that triggers turbulence in a voluteless fan, which is a benchmark configuration for HVAC air units. A region of relatively small flow velocity rotates within the fan clearance passage, and turbulence commences downstream of this region.…”
mentioning
confidence: 99%
“…By adjusting the ejector geometry, experiments and numerical simulations showed that the thrust was increased, but the specific fuel consumption and noise emissions were reduced. In addition to the above works, Ottersten et al [9] found a new mechanism that triggers turbulence in a voluteless fan, which is a benchmark configuration for HVAC air units. A region of relatively small flow velocity rotates within the fan clearance passage, and turbulence commences downstream of this region.…”
mentioning
confidence: 99%